Politica fiscal-bugetară din perspectiva procesului de integrare europeană - Dorin Măntescu (Romanian Journal of European Affairs)
2003 was the best year in a transition decade from the point of view of the macroeconomic performance. Also, the structural reforms were consistent, wage policy was cautious and the first IMF agreement was concluded from the point of view of the implementation. However, notwithstanding the progress, Romania is still confronted with substantial structural problems in energy, railways and mining sectors. Furthermore, the large share of the total population that lives in the rural areas and the situation of the pension system represent additional major structural constraints that we currently face. The speed up of these reforms will require additional public expenditures. Additional public resources need to be channeled also in health, education, infrastructure and institutional reform areas. The level of public expenditures in România was around 32,7 percent of GDP in 2002 compared to over 45 percent in the other more advanced candidate countries and EU member states. There are two reasons for this lower expenditure level as percent of GDP: the lower level of public revenues as percent of GDP and the lower level of budget deficit. Given the additional expenditure needs, România should do the best effort to increase public revenues by improving tax collection, enlarging the tax base and cutting social security tax rates. Also given the lower levels of the budget deficit and public debt from a comparative perspective, România should increase the budget deficit. Taking into account that the larger public sector deficit is composed from the consolidated budget deficit and the arrears and losses in the public enterprises, an increase of the budget deficit accompanied by a larger decrease of the arrears and losses in the public owned enterprises will allow the reduction of the overall excess aggregate demand. This will help us to maintain the disinflationary tendency that our economy knew in the last several years while benefitting of additional public expenditures.